Negative Associations of Stress and Anxiety Levels With Cytotoxic and Regulatory Natural Killer Cell Frequency in Chronic Tinnitus - Basso, Laura; Boecking, Benjamin; Neff, Patrick; Brueggemann, Petra; El-Ahmad, Linda; Brasanac, Jelena; Rose, Matthias; Gold, Stefan M.; Mazurek, Birgit (Frontiers in Psychology, 2022)
Background: Depression and anxiety are known to be associated with stress-induced changes in the immune system. Bothersome tinnitus can be related to stress and often co-occurs with depression and anxiety. This study investigates associations of psychological and audiological tinnitus-related factors with inflammatory parameters and immune cell subsets in chronic tinnitus patients as well as treatment-related effects. Methods: This longitudinal study of inpatients treated with compact multimodal tinnitus-specific cognitive behavioral therapy included four repeated measurement sessions: baseline (N=41), treatment end, 7.8-week (N=35), and 13.8-week follow-up (N=34). Data collection included audiometric testing, blood sampling, and psychometric questionnaires: Tinnitus Handicap Inventory (THI), Perceived Stress Questionnaire (PSQ-20), and Hospital Anxiety Depression Scale (HADS). Flow cytometry was used to analyze immune cell subsets. Statistical analyses comprised correlation and network analysis (cross-sectional), and linear mixed effect models (longitudinal). Results: Bootstrapped network analysis showed negative averaged cross-sectional associations of cytotoxic natural killer (NKc) cell frequency (CD56+CD16+) and PSQ-20 (-0.21 [-0.48, 0]) and of regulatory natural killer (NKreg) cell frequency (CD56+CD16dim/-) and HADS anxiety (-0.14 [-0.38, 0]). No significant treatment effects were found. A negative predictive effect of baseline PSQ-20 scores (β=-6.22 [-12.18, -0.26], p=0.041) and a positive predictive effect of baseline ferritin levels (β=8.90 [2.76, 15.03], p=0.004) on NKc cell frequency across the repeated measurement sessions were observed. Conclusions: We observed negative relationships between perceived stress levels and NKc cell frequency and between anxiety levels and NKreg cell frequency in chronic tinnitus patients. These exploratory results suggest stress-/anxiety-related immune alterations in bothersome tinnitus but need to be tested in further confirmatory studies with larger sample sizes. The potential of NK cells as biomarkers of emotional distress in chronic tinnitus should be further investigated.